RELATIONSHIP OF MUTATION OF KODON S 315 T KATG MYCOBATERIUM TUBERCULOSIS GENE WITH MULTIDRUG RESISTANCE TUBERCULOSIS IN SOUTH SUMATERA - Syafriani, Diah; Pasaribu, Rouly Pola; Ahmad, Zen (Biomedical Journal of Indonesia, 2020)
MDR TB is a condition of M. tuberculosis that is resistant to isoniazid and rifampicin. This occurs because of certain genomic mutations in certain Mtb specific genes. Some of the genes that play a role in the INH mutation are the katG gene, the inhA gene, the ahpC gene, the ndh gene and the kasA gene. The most frequent mutation gene is the katG gene, around 50-80%, and the most mutations (64%) are found in the S 315T codon. The aim was to determine the relationship of S315T genotype in the M. tuberculosis katG gene with the incidence of Mtb resistance in MDR TB patients in South Sumatra. This type of research is an observational cross sectional study approach, conducted in Palembang RSMH in collaboration with the Clinical Microbiology Laboratory of FK UNSRI Palembang from January - July 2019. The sample of the case group (MDR TB) was 50 people while the control group (TB SO) was 21 people. Each group was tested for S315T genotype katG M. tuberculosis gene using the PCR-RFLP method with the Mspl enzyme. Visualization of the katG gene in codon 315 in this study was only found in 40 samples, 26 samples in the case group (MDR TB) and 14 samples in the control group (TB SO). Results Genetic frequency distribution in the case group (MDR TB) was 65.38% wildtype and 34.62% mutant, whereas in the control group (TBSO) it was 92.86% wildtype and 7.14% mutant. The 315 coded KatG gene mutation in this study was not related to the incidence of MDR TB, with p = 0.07, an odds ratio of 6.8 (0.77 - 61.40, 95% CI). The conclusions of this study found 315G katG M. tuberculosis codon mutation mutations of 34.62% but not significantly related to the incidence of MDR TB in South Sumatra.